2013
DOI: 10.1038/ncomms2825
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive selection of target DNA sequences by synthetic bZIP peptides

Abstract: One of the strategies used by nature to regulate gene expression relies on the stimulicontrolled combination of DNA-binding proteins. This in turn determines the target-binding site within the genome, and thereby whether a particular gene is activated or repressed. Here we demonstrate how a designed basic region leucine zipper-based peptide can be directed towards two different DNA sequences depending on its dimerization arrangement. While the monomeric peptide is non-functional, a C-terminal metallo-dimer rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 47 publications
(47 reference statements)
1
20
0
Order By: Relevance
“…Additionally, an N‐terminal cap, acetamido benzoic acid (Aba) was added to the N‐terminus of the peptide. This aromatic moiety allows convenient UV‐monitoring and concentration determination as an internal standard,17b while efficiently blocking the N‐terminus during the introduction of the second amino acid sequence (Scheme ). We chose to immobilize earlier described and well‐studied GCN4 basic‐region peptides as DNA‐binding moieties from the simple bZIP rather than b‐HLH‐ZIP TF family.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, an N‐terminal cap, acetamido benzoic acid (Aba) was added to the N‐terminus of the peptide. This aromatic moiety allows convenient UV‐monitoring and concentration determination as an internal standard,17b while efficiently blocking the N‐terminus during the introduction of the second amino acid sequence (Scheme ). We chose to immobilize earlier described and well‐studied GCN4 basic‐region peptides as DNA‐binding moieties from the simple bZIP rather than b‐HLH‐ZIP TF family.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we exploited this feature to demonstrate the ability of HCM-bearing peptides to recognize and bind a biological target. Starting with the pioneering work by Kim, 54,61 several synthetic strategies have been developed for the dimerization of bZIP peptides, 55,62-64 including disulfide bonding, 54 metal coordination, 65-68 and crosslinking with metal-tunable 69 or photo-switchable linkers. 70-72 These studies have collectively shown the importance of the dimeric organization of the basic domains as well as their proper orientation for DNA binding and recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Building on this successful idea of miniaturisation, Morii, Schepartz, Mascareñas Q3 and our group have enforced the proof-of-concept by using a variety of small dimerizing moieties. [7][8][9][10][11][12] Subsequently, we have shown that the attachment of the basic region peptides to a rigid scaffold, a derivative of deoxycholic acid in this case, also allows selective recognition of DNA. Indeed, our previous work on cMyc-Max b-HLH-ZIP and GCN4-bZIP proteins showed that this type of steroid-based constructs show potential for binding DNA.…”
Section: Q4mentioning
confidence: 99%